2017
DOI: 10.1111/jgs.15048
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction Predicts Subsequent Dementia in Older U.S. Adults

Abstract: Objectives To investigate the relationship between olfactory dysfunction and subsequent diagnosis of dementia. Design Longitudinal study of a population representative of U.S. older adults. Setting Home interviews (National Social Life, Health, and Aging Project). Participants Men and women aged 57 to 85 (N = 2,906). Measurements Objective odor identification ability was measured at baseline using a validated five‐item test. Five years later, the respondent, or a proxy if the respondent was too sick to intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 28 publications
5
62
0
Order By: Relevance
“…In one study with 5 years of follow‐up time, those with OI compared to those without OI at baseline had a significantly increased odds of developing incident dementia (adjusted OR = 2.13, 95% CI 1.33–3.69) . In another study, decrease in the 13‐item SOIT score was associated with higher risk of developing dementia at 10 years (adjusted OR = 1.12, 95% CI 1.02–1.23) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In one study with 5 years of follow‐up time, those with OI compared to those without OI at baseline had a significantly increased odds of developing incident dementia (adjusted OR = 2.13, 95% CI 1.33–3.69) . In another study, decrease in the 13‐item SOIT score was associated with higher risk of developing dementia at 10 years (adjusted OR = 1.12, 95% CI 1.02–1.23) .…”
Section: Resultsmentioning
confidence: 99%
“…One of these determined incident dementia using clinical diagnosis with Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM‐IV), criteria . Another study used medical record abstraction and/or ≥1.5 SD decline in Modified MMSE compared with cohort's race‐matched mean change in score, whereas the third study used self‐ or proxy‐reported diagnosis of dementia …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations